PROFIL USAHA AGROINDUSTRI SUSU KEDELAI RESOYA DI KECAMATAN MALALAYANG - Irhandi Turnip; Ventje V. Rantung; Theodora M. Katiandagho; Vicky R.B. Moniaga (COCOS, 2015)
ABSTRACT This objective of this research to determine the profile of soy milk resoya agroindustrial enterprises. This study uses primary data collected through direct interview techniques to business owners. Data analysis method used in this research is descriptive data analysis. The data collected are presented in tables and used the analysis of cost, revenue, profit, and also the analysis of break-even point. These results indicate that these efforts received a profit of Rp. 2,709,542 during the month of production. The results of the analysis of break-even point in this effort, at the time of soy milk production volume amounted to 75 glasses resoya namely to 5 times the production process. Business owners foresight in looking at market opportunities led to this business is quite promising and could add to the family income. Based on this study it can be concluded that this resoya soy milk business Established in May 2011 registered P.IRT No. 2137171010641- 19 and belonging to the domestic industry, does not have the books. Business organizational structure is very simple. Raw and auxiliary materials derived from the capital market and also market supermarket golden shoulder. Venture capital comes from their own capital. Volume production of an average of 363.5 glasses per week. Marketing of soy milk that is at Freshmart, Supermarkets Borobudur, Gelael Supermarket, Restaurant Ranto Minang, food stalls Malalayang hospital, and the Manado Adventist Hospital. Fixed cost depreciation tool Rp. 149,138.88, while the variable cost of Rp. 3.68432 million and a total cost of Rp. 383.3458.9. Total revenue of this business is Rp. 6.543 million and total profit as Rp.2.709.542. The ratio of R / C 1.7 which means that the business is feasible to be developed.